Effect of Competence on Employee Productivity at PT Socfindo Indonesia Pamingke - Geby Ardiana; Pretty Failasufa Aziza (Budapest International Research and Critics University, 2022)
Research aims to determine the effect of Competence on Employee Productivity at PT. Socfindo Indonesia Pamingke. Respondents in this study were 73 people. This study uses quantitative research with sampling using a sampling that is purposive sampling. Data was collected by distributing questionnaires in the form of a statement questionnaire to 73 respondents. The results of this study through a simple linear regression test are indicated by Y=28,200+0.207x, with a regression coefficient value of x worth 0.207 which means that for every 1% addition to the value of the competency variable (x), the productivity variable (y) increases by 0.207 or 20, 7%. The results of the t-test = 3.489 > t table = 1.994 and the significance value is 0.001 <0.05 so it can be concluded that Ho is accepted and Ha is rejected.